Microemulsion-made gadolinium carbonate hollow nanospheres showing magnetothermal heating and drug release. Issue 24 (8th June 2017) - Jung-König, J.; Sanhaji, M.; Popescu, R.; Seidl, C.; Zittel, E.; Schepers, U.; Gerthsen, D.; Hilger, I.; Feldmann, C.
Abstract : Gadolinium carbonate (Gd2 (CO3 )3 ) hollow nanospheres and their suitability for synergistic magnetothermally-induced heating and drug release are presented. Abstract : Gadolinium carbonate (Gd2 (CO3 )3 ) hollow nanospheres and their suitability for drug transport and magnetothermally-induced drug release are presented. The hollow nanospheres are prepared via a microemulsion-based synthesis using tris(tetramethylcyclopentadienyl)gadolinium(iii ) and CO2 as the starting materials. Size, structure and composition of the as-prepared Gd2 (CO3 )3 hollow nanospheres are comprehensively validated by several independent analytical methods (HRTEM, HAADF-STEM, DLS, EDXS, XRD, FT-IR, DTA-TG). Accordingly, they exhibit an outer diameter of 26 ± 4 nm, an inner cavity of 7 ± 2 nm, and a wall thickness of 9 ± 3 nm. As a conceptual study, the nanocontainer-functionality of the Gd2 (CO3 )3 hollow nanospheres is validated upon filling with the anti-cancerogenic agent doxorubicin (DOX), which is straightforward via the microemulsion (ME) strategy. The resulting DOX@Gd2 (CO3 )3 nanocontainers provide the option of multimodal imaging including optical and magnetic resonance imaging (OI, MRI) as well as magnetothermal heating and drug release. As a proof-of-concept, we could already prove the intrinsic DOX-based fluorescence, a low systemic toxicity according to in vitro studies as well as the magnetothermal effect and a magnetothermally-induced DOX release. In particular, the latter is new for Gd-containing nanoparticles and highly promising in view of theranostic nanocontainers and synergistic physical and chemical tumor treatment.